METHODS FOR DEMONSTRATING THE VALUE OF PUBLIC LIBRARIES IN THE UK: A LITERATURE REVIEW - ROONEY-BROWNE, University of Strathclyde , Christine (BIBLIOPOLIS, 2020)
This paper summarises the findings of a report commissioned by the Chartered Institute of Library and Information Professionals’ (CILIP) Library and Information Research Group (LIRG) realized in order to produce a comprehensive review of existing quantitative and qualitative evaluation methodologies for demonstrating the value of public libraries in the United Kingdom (UK). A thorough literature review of existing research was carried out and an investigation into best practices for evaluating impact was conducted. A wide range of journals and books published within the fields of library and information science and social research have been consulted. Relevant White Papers and Reviews; such as those published by the Chartered Institute of Library and Information Professionals (CILIP), the Scottish Library and Information Council (SLIC); the Museums, Libraries and Archives Council (MLA), the Department of Culture, Sport and Media (DCMS); and the American Library Association (ALA) have been analysed. It is anticipated that the fi ndings of this research will help the sector to develop more appropriate models for demonstrating the value of public libraries in the 21st century. The original report was compiled in June 2010.